Pengaruh Pemberian Quadriceps isometric exercise terhadap perubahan nyeri osteoarthritis knee pada pasien Rumah Sakit Wijaya Kusuma Lumajang - Anggi Kurniawati; Nurul Halimah; Rachma Putri Kasimbara; Angria Pradita (Jurnal Keperawatan Muhammadiyah, 2023)
Knee osteoarthritis is a disorder of the knee joint that is progressive, for example in the joint cartilage, synovial fluid and subchondral bone, and causes furs, ulcerations, and becomes thin. The main complaints that are often felt by sufferers of Knee Osteoarthritis are pain, limited range of joint motion, mechanical abnormalities, and limitations in carrying out daily functional activities. Complaints felt by sufferers of Knee Osteoarthritis can cause a decrease in the quality of life in the elderly. This study aims to identify the effect of quadriceps isometric exercise on changes in pain in osteoarthritis patients. This research has 21 respondents. The research design uses a pre-experimental type with a one group pretest and posttest approach. Bivariate analysis in this study used Wilcoxon. The results of this study were that the mean pain scale before quadriceps isometric exercise was 5.761, the mean pain scale after quadriceps isometric exercise in knee osteoarthritis patients was 2.857, and there was an effect of isometric quadriceps exercise on reducing pain in osteoarthritis patients at Wijaya Kusuma Hospital Lumajang with a p-value = 0.000 (p<0.05). It is hoped that this research can provide additional information based on data and theory to improve the quality of physiotherapy services by establishing a standard procedure for performing the quadriceps isometric exercise, especially in osteoarthritis patients.